COMBATING PATHOGENIC MICROBES THROUGH E. COLI BASED SILVER NANO TOOLS - VANDANA SINGH; ARCHANA TIWARI (International Journal of Pharma and Bio Sciences, 2016)
The enhancing number of antibiotic-resistant bacteria calls for exploring new antimicrobial agents. “Silver nanoparticle", has captured the attention of the scientific community because of its recognized antimicrobial activity. This study was aimed to evaluate the antibacterial effects of E. coli origin (biologically synthesized) silver nanoparticles on different bacterial and fungal strains. Pathogenic bacteria and fungi namely Staphylococcus aureus, Bacillus cereus, Pseudomonas aeruginosa, Klebsiella pneumonia, Salmonella typhi, Candida albicans and Aspergillus niger were used in this study. All strains were inoculated uniformly onto sterile Muller-Hinton Agar plates using sterile cotton swabs (lawn inoculation method). Wells of 06 mm diameter were bored into the agar medium using sterile borer. 100 µl silver nanoparticles solution was added into each well and after incubation at 37°C for 24 hours and different inhibition zones were measured. Sterilized Nutrient Broth was used as negative control. The determinations were done in triplicate and the mean values ± SD were calculated and presented in graphical form. The inhibition zones (diameters in mm) measured for Gram positive bacteria, Staphylococcus aureus was 15.03 ± 0.20 mm and Bacillus cereus was 15.16± 0.25 mm, whereas for Gram negative bacteria, Klebsiella pneumonia was 15.26 ± 0.47 mm and Salmonella typhi was 19.16 ± 0.55mm. Against fungi Aspergillus niger and Candida albicans, the inhibition zones measured were 16.6 ± 1.52 and 9.6 ± 1.15 mm respectively. On the other hand negative control does not show any inhibitory zones. AgNPs have immense potential to act as an antimicrobial agent and can efficiently address the problem of drug resistance.